The birthday ball [compact disc, unabridged] - Lowry, Lois (Random House/Listening Library, 2010)
When a bored Princess Patricia Priscilla makes her chambermaid switch identities with her so she can attend the village school, her attitude changes and she plans a new way to celebrate her sixteenth birthday.